Part I: Synthesis, characterization and reactivity studies on Ir(III) and Ru(IV) complexes with sulfur ligands. Part II: Catalytic applications of Ru and Pd metallacycles in C-C and C-P bond formations - Xu, Chang (2012)
The thesis is divided into two parts. Part I: Synthesis, Characterization and Reactivity studies on Ir(III) and Ru(IV) Complexes with Sulfur Ligands. Investigations into the reactivity of [Cp*Ir(η3-C4H8S3)] (1) in the role of metallo-ligand towards other organometallic species and alkylating reagents will be discussed. The catalytic potential of 1 in low catalyst loading and additive free β-alkylation reactions involving alcohols and in a highly selective imine synthesis protocol (via catalytic N-alkylation of amines with alcohols) will be presented. Results from the reactivity studies of [{(η3:η3-C10H16)Ru(-Cl)Cl}2] with dithiuram disulfides [R2NC(S)S-]2 (R = Me, iPr) and thiuram monosulfide will also be discussed. Part II: Catalytic Applications of Ru and Pd Metallacycles in C-C and C-P Bond Formations. A novel ruthenacycle catalyzed one-pot β-alkylation of alcohols which tolerates non-traditional substrates was developed. An efficient one-pot synthesis of 2,3-substituted indoles via domino cyclization/alkylation reaction of 2-alkynylanilines with allylic alcohols was also investigated. A highly enantio-selective asymmetric synthesis of chiral monophosphine ferrocenyl (MOPF) ligands and diester functionalized tertiary phosphines will also be discussed. Mechanistic insights from the aforementioned catalytic protocols will be presented.